Quality management system: A model to consolidate OBE and stakeholders requirement / Asmidar Alias … [et al.] - Alias, Asmidar; Mohsan, Nor Maslina; Abdul Latib, Farah Wahida; Khalid, Khairi (2011)
Issue in quality control and reporting adequate data for various stakeholders have been the center of discussion in Faculty Of Civil Engineering (FCE) UiTM Pahang since 2006. The implementation of Outcome Based Education (OBE) required planning, implementation, assessment and continual quality improvement (CQI), thus comprehensive data management is essential. However, FCE UiTM Pahang has been requested with different types of data and reporting styles responding to various stakeholders. Repeating and redundant processes encountered by faculty members to fulfill this requirement is tedious and time consuming. A model for quality management system (QMS) to consolidate these requirements is formulated to alleviate difficulties and minimize complexity during audit practices. The processes, approach, specific requirement involved for this exercise are discussed, which highlight the salient aspect of the problems.